Journey to Jo'burg a South African story - Naidoo, Beverley; Velasquez, Eric (New York HarperTrophy, 1988)
Separated from their mother by the harsh social and economic conditions prevalent among blacks in South Africa, thirteen-year-old Naledi and her younger brother make a journey of over 300 kilometers to find her in Johannesburg.
Keywords: Blacks -- South Africa -- Fiction; South Africa -- Race relations -- Fiction